Epidemiology of banana bunchy top disease in South Sumatra, Indonesia - Arsi Arsi; Suparman Suparman; Yulia Pujiastuti; Chandra Irsan (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Banana bunchy top disease has become increasingly important in South Sumatra. The disease, caused by Banana bunchy top virus (BBTV), leads to severe losses as infected plants fail to produce fruit. The virus is transmitted in a persistent manner by banana aphid, Pentalonia nigronervosa. Both nymphs and adults of the aphid can transmit the virus, with adults being more efficient vectors than nymphs. The threat of the disease in the province has been escalating, as indicated by the significant rise in the number of infected banana plants in the recent years. However, no epidemiological study had been conducted prior to this research. This study aimed to identify and evaluate the contributing factors to the epidemic of banana bunchy top disease in South Sumatra. A survey was conducted to assess the banana cropping system and all aspects contributing to the disease’s epidemiology in the province. Thirteen regencies were surveyed using a purposive sampling method, covering 11 regencies and 3 cities selected based on the accessibility of banana plantations by transportation routes. In each site, banana plants within an imaginary 50-meter diameter circle centered on an infected plant were sampled. The result showed that the BBTV epidemic was influenced by several factors: (1) banana genome, with diploid AA and triploid AAA cultivars being more resistant than those containing the B genome; (2) cropping system, with higher disease prevalence in mixed-cropping systems than in monoculture; (3) botanical environment, where the presence of alternative hosts of P. nigronervosa correlated with higher disease incidence; (4) farmer behavior, with lack of concern or action against the disease contributing to its spread; and (5) transportation access, with higher incidence observed in areas closer to roads.